Basic Arabic : a grammar and workbook - Samy, Waheed; Samy, Leila (New York : Routledge, 2014)
'Basic Arabic: A Grammar and Workbook comprises an accessible reference grammar with related exercises in a single volume.This book presents 51 units, covering the key grammar points which students would expect to encounter in their first year of learning Arabic. Examples and exercises are provided throughout, allowing students to reinforce and consolidate their learning.Key features include:Clear, accessible formatMany useful language examplesJargon-free explanations of grammarAbundant exercises with full answer keySubject indexClearly presented and user-friendly, Basic Arabic is an ideal grammar reference and practice resource for both beginners and students with some knowledge of the language. It is suitable for both class use and independent study.'-- c Provided by publisher.
Keywords: Arabic language -- Grammar -- Problems, exercises, etc; Arabic language -- Textbooks for foreign speakers -- English; Arabic language -- Grammar; Arabic language -- Self-instruction